Penggunaan Telemedicine terhadap Peningkatan Kepuasan Pasien dalam Layanan Kesehatan di Indonesia : Systematic Review - Nuryuliana Nuryuliana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Background: Patient satisfaction is a form of feeling happy or disappointed with the service received after the patient compares it with what is expected. In the era of digitalization, telemedicine has an impact on health services, especially patient satisfaction. This study aims to determine the use of telemedicine on increasing patient satisfaction in health services in Indonesia. Research methods: Systematic review using PRISMA guidelines and the PICO model, Population = patients who use telemedicine; Intervention = telemedicine; Comparison = not using telemedicine; Outcome = patient satisfaction in health services in Indonesia. Articles were collected through Google Scholar, Jurnal Manajemen Kesehatan (JMK), Jurnal Kebijakan Kesehatan Indonesia (JKKI), Jurnal Pendidikan dan Teknologi Kesehatan (JPTK), Jurnal Ilmiah Indonesia (JII), and Jurnal Komunikasi which focus on Indonesia. Keywords use: patient satisfaction, health services, telemedicine, Indonesia. A total of 6 articles met the inclusion criteria for a systematic review. Results: 6 articles out of 119 articles were studied for systematic review. Six articles did not find a significant difference in patient satisfaction between telemedicine and face-to-face meetings. There are several factors that influence patient satisfaction, including: most are female, productive age, college educated, and work as private employees. Conclusion: Telemedicine services have been shown to increase patient satisfaction in health services in Indonesia. This shows that the more telemedicine services used, the higher the level of patient satisfaction. However, further research is needed to analyze how effective the use of telemedicine is on patient satisfaction in health services in Indonesia.